Poverty and Social Impact Analysis in PRGF-Supported Programs - Inchauste, Gabriela (IMF Policy Discussion Papers; Policy Discussion Paper, 2002)
This paper aims to inform on the status of Poverty and Social Impact Analysis (PSIA) in IMF-supported programs, detailing the results presented in the recent review of PRGF-supported programs. The review showed that more needs to be done, both in undertaking PSIA when necessary, and in reporting the policy tradeoffs in program documents. Policy design should be continuously informed by the results of PSIA.